Pemberian Pakan Ikan Otomatis Pada Akuarium Menggunakan Nodemcu Esp8266 - Kiki Julita Ningsih; Linna Oktaviana Sari; Ery Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Keeping various types of ornamental fish in the aquarium must be considered when maintaining one of them is in feeding fish. For some people who have quite a lot of hectic activities, it can be a difficult task to handle fish feed when leaving the house for extended periods. Therefore, a system was designed to assist aquarium owners in regular feeding of fish, and aquarium owners can monitor fish feeding remotely. This tool works according to the fish feed schedule with a frequency of twice a day, in the morning and evening. This study uses software and hardware consisting of ESP8266 as the main control, ultrasonic sensor as a feed distance meter, servo motor as a container valve opener, RTC (Real Time Clock) as a scheduler, and a buzzer as an alarm. When the internet is connected to the ESP8266, the data will be sent to a telegram to notify the owner. Based on the test results, this fish feeding tool can work according to a pre-arranged schedule option, and is able to display notifications to the telegram application. The system that has been designed can already monitor the feeding of fish and provide notification results in the form of information on the availability of fish feed and notification of the feeding schedule for fish through the telegram application on the user's smartphone.Keywords : ESP8266, Internet of Things, Telegram